Rekognisi Publik Pengguna Pelayanan Akuntan Terhadap Tingkat Moralitas Akuntan Publik - Muhammad Reza Ramdani; Ismi Ayu Lestari (ITB AAS INDONESIA, 2019)
This study aims to determine the public Recognition of public accountant service users to the level of Morality of public accountants. Where the public users of public accounting services or the users of financial statements consists of internal parties represented by directors or managers of companies go public and external parties represented by investors and creditors who are respectively securities firms and conventional banks in the city of Makassar. The research method used descriptive qualitative approach through the process of observation and spreading questionnaire (questionnaire). Primary data obtained through the distribution of questionnaires to respondents public users of public accounting services. The rate of return of questionnaires was 95.3% or 41 questionnaires from 43 questionnaires distributed. The result of the research shows that public perception of public accountant service user to integrity of public accountant either show positive value or most give answer agree on questionnaire sheet. So this research concludes that public perception of public accountant service user to integrity level of public accountant in Makassar city is positive or still in high level of integrity.